New insights on molecular interactions of organophosphorus pesticides with esterases - Mangas, Iris; Estevez, Jorge; Vilanova, Eugenio; França, Tanos Celmar Costa (Toxicology, 2017)
Organophosphorus compounds (OPs) are a large and diverse class of chemicals mainly used as pesticides and chemical weapons. People may be exposed to OPs in several occasions, which can produce several distinct neurotoxic effects depending on the dose, frequency of exposure, type of OP, and the host factors that influence susceptibility and sensitivity. These neurotoxic effects are mainly due to the interaction with enzyme targets involved in toxicological or detoxication pathways. In this work, the toxicological relevance of known OPs targets is reviewed. The main enzyme targets of OPs have been identified among the serine hydrolase protein family, some of them decades ago (e.g. AChE, BuChE, NTE and carboxylesterases), others more recently (e.g. lysophospholipase, arylformidase and KIA1363) and others which are not molecularly identified yet (e.g. phenylvalerate esterases). Members of this family are characterized by displaying serine hydrolase activity, containing a conserved serine hydrolase motif and having an alpha-beta hydrolase fold. Improvement in Xray-crystallography and in silico methods have generated new data of the interactions between OPs and esterases and have established new methods to study new inhibitors and reactivators of cholinesterases. Mass spectrometry for AChE, BChE and APH have characterized the active site serine adducts with OPs being useful to detect biomarkers of OPs exposure and inhibitory and postinhibitory reactions of esterases and OPs. The purpose of this review is focus specifically on the interaction of OP with esterases, mainly with type B-esterases, which are able to hydrolyze carboxylesters but inhibited by OPs by covalent phosphorylation on the serine or tyrosine residue in the active sites. Other related esterases in some cases with no-irreversible effect are also discussed. The understanding of the multiple molecular interactions is the basis we are proposing for a multi-target approach for understanding the organophosphorus toxicity.
Keywords: Animals; cholinesterasy; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Organophosphorus Compounds; cholinesterases; vazba proteinů; lidé; pesticidy; Organophosphorus compounds; alpha/beta hydrolases; Cholinesterases; Esterases; organofosforové sloučeniny; pesticides; krystalografie rentgenová; mass spectrometry; Protein Structure, Secondary; sekundární struktura proteinů; Pesticides; esterasy; spektrometrie hmotnostní - ionizace laserem za účasti matrice; zvířata; Crystallography, X-Ray; in silico; Protein Binding; Humans